A Pantropical Analysis of Fire Impacts and Post‐Fire Species Recovery of Plant Life Forms - Dharma P. Sapkota; David P. Edwards; Mike R. Massam; Karl L. Evans (Ecology and Evolution)
ABSTRACT Fires are a key environmental driver that modify ecosystems and global biodiversity. Fires can negatively and positively impact biodiversity and ecosystem functioning, depending on how frequently fire occurs in the focal ecosystem, but factors influencing biodiversity responses to fire are inadequately understood. We conduct a pan‐tropical analysis of systematically collated data spanning 5257 observations of 1705 plant species (trees and shrubs, forbs, graminoids and climbers) in burnt and unburnt plots from 28 studies. We use model averaging of mixed effect models assessing how plant species richness and turnover (comparing burnt and unburnt communities) vary with time since fire, fire type, protected area status and biome type (fire sensitive or fire adaptive). Our analyses bring three key findings. First, prescribed and non‐prescribed burns have contrasting impacts on plant species richness (trees/shrubs and climbers); prescribed fire favours increased species richness compared to non‐prescribed burns. Second, the effect of time since fire on the recovery of species composition varies across all life form groups; forb's species composition recovered faster over all life forms. Third, protection status alters fire impacts on the species richness of trees/shrubs and climbers and species recovery of graminoids. Non‐protected areas exhibit higher species richness compared to protected areas in trees/shrubs, and climbers. Graminoid species composition recovered quicker in protected sites compared to unprotected ones. Since fire intervals are decreasing in fire‐sensitive biomes and increasing in fire‐adaptive biomes, plant communities across much of the tropics are likely to change in response to exposure to fire in the future.